Pengaruh Karakter Eksekutif, Pertumbuhan Penjualan, dan Ukuran Perusahaan Terhadap Tax Avoidance - Agustin Dwi Haryanti (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2021)
This study aims to determine the effect of executive character, sales growth, and company size on tax avoidance. The research objects are property, real estate, and building construction companies listed on the Indonesia Stock Exchange (IDX) with a total of 81 companies. This research uses financial statements for the 2019-2020 period. The sample selection was based on a purposive sampling technique which resulted in 43 companies. Data analysis using SPSS to test the relationship between a variable with other variables. Research shows that executive characteristics and firm size have a positive effect on tax avoidance. Another independent variable, sales growth has no effect on tax avoidance.